RADIO SENSITIVITY AND INDUCTION OF SEXUAL STERILITY IN CUCURBIT FRUIT FLY DACUS CILIATUS (LOEW): I- IRRADIATION OF EGGS AND LARVAE - Yousif, G.; AL-Azzawi, B.; AL-Rubeai, H.; Hamad, B. (Iraqi Journal of Science, 2024)
The results of the present investigation indicated that exposing the eggs of Dacus ciliatus to incremented doses of gamma ray, showed that eggs were highly sensitive. The hatchability was significantly reduced with the increase of doses, in comparison with the control treatment.The negative effect of irradiation was continued to the subsequent developmental stages, and on adult emergence and longevity. The dose of 10 Gy reduced significantly the fecundity and hatchability at all mating types, and there was no potential to induce complete sterility in the emerged adults. Prepupal larvae were less radiosensitive than the eggs. Adult emergence at 10 and 20 Gy was 88 and 56% respectively. The fecundity was reduced significantly in two mating types at 10 and 20 Gy. Hatchability of all types of mating was reduced significantly at 20 Gy; hence it did not reach to the level of induction of complete sexual sterility.